Deuterium retention in tungsten under the combined influence of displacement damage and helium - Ting Wang; Xiu-Li Zhu; Mengchong Ren; Yue Yuan; Wangguo Guo; Shiwei Wang; Long Cheng; Di Hu; Yuhao Li; Guang-Hong Lu (Nuclear Fusion)
Accurate predictions of hydrogen isotope/tritium inventory in tungsten (W), used as a plasma-facing material in fusion reactors, can reduce the uncertainty associated with the self-sustaining fuel cycle. It is well-established that displacement damage generally enhances deuterium (D) retention in W, whereas helium (He) typically reduces it. However, the synergistic interaction between these two factors on D retention in W remains poorly understood. This study investigates the combined influence of displacement damage and plasma-implanted He on D retention in W, with focus on their dependence on D-induced blistering. High-energy (3.5 MeV) Fe ^13+ irradiations were conducted at 300 K to introduce displacement damage (0.1 dpa) in W. Low-energy (60 eV) He plasma exposure was then carried out at 600 K to generate a He-rich layer at the near surface of both pristine and Fe-irradiated samples. Subsequently, the samples were exposed to D plasma at 500 K, with the ion energy set to 38 eV. The results show that displacement damage increases D retention at low fluences (5 × 10 ^24 –1 × 10 ^25 D m ^−2 ), but slightly decreases retention at higher fluences (3 × 10 ^25 –5 × 10 ^25 D m ^−2 ). The impact of He on D retention in W is competitive, depending on the level of irradiation damage. In cases with minimal D-induced blistering (area ratio <13%), the trapping effect dominates, with He-induced defects acting as strong D traps, leading to increased D retention. However, in highly damaged W, where high-density defects are induced by displacement damage or severe surface blistering (area ratio >33%), the diffusion barrier effect of He-rich layer outweighs the trapping effect, leading to decreased D retention. The combined effect of displacement damage and He increases D retention at low D fluences and decreases it at high D fluences, with the magnitude of these changes deviating from a simple linear addition of their individual effects, indicating a complex, non-linear interaction.